The Other Side of the Coin: can Turkey ''Get'' West by Oil? - Bestenigar KARA; Alexandru GRIBINCEA; Lilia SHARGU (Eastern European Journal of Regional Studies)
This study shortly brings forward the oil situation of the world and Turkey's current role in this picture. Within this frame subjects of article have been searched in depth as follows: the current oil status of the world in terms of proven reserves, production, consumption and trade, insufficient use of renewables as against oil, main reasons changing the balances in global oil market. The topic of article is and has always been a current issue. Oil has always come to the forefront taking into account for example oil crises throughout history, the global developments together with new technologies or growing population together with increasing energy demand alongside of its wide range of use in different sectors from textile to transportation. On this basis the aim of article was to reveal how in fact developed but oil poor regions are relied on oil rich but developing regions and Turkey's importance as a transit country within the context of supply for oil poor regions.